2008
DOI: 10.1039/b808049f
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic-containing hydrocarbons: natural compounds in oil from the fish capelin, Mallotus villosus

Abstract: Arsenic-containing hydrocarbons have been identified for the first time as natural components of fish oil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
110
0
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 109 publications
(116 citation statements)
references
References 8 publications
3
110
0
3
Order By: Relevance
“…2. Arsenic-hydrocarbons in Wakame and Hijiki; As-HC332 & As-HC360, previously identified in fish oil [7] and sashimi tuna, [9] were present in both Wakame and Hijiki. The homologue As-HC388 is first reported here where it was shown to be present in Wakame (but not Hijiki).…”
Section: Asmentioning
confidence: 97%
See 2 more Smart Citations
“…2. Arsenic-hydrocarbons in Wakame and Hijiki; As-HC332 & As-HC360, previously identified in fish oil [7] and sashimi tuna, [9] were present in both Wakame and Hijiki. The homologue As-HC388 is first reported here where it was shown to be present in Wakame (but not Hijiki).…”
Section: Asmentioning
confidence: 97%
“…[1] Although most of the arsenic compounds identified so far have been water-soluble species, the early work on arsenic marine chemistry focussed on lipidsoluble compounds, so called arsenolipids. [2][3][4] Identification of these arsenolipids proved difficult, however, and it was not until 1988 that an arsenolipid was first rigorously characterised and identified as an arsenosugar-containing phospholipid [5] (see Table 1, compound As-PL958).Subsequently, the range of naturally occurring arsenolipids has been extended with the discovery of arsenic-containing fatty acids in fish oils, [6] and arsenic-containing hydrocarbons in fish oils, [7] fish liver, [8] sashimi tuna [9] and fish meal. [10] The origin of these compounds was presumed to be algae.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Combined use of elemental and molecular mass spectrometry is helpful to identify the arsenic-containing non-polar compounds and elucidate their structure. By using combined HPLC-ICP-MS and HPLC-electrospray ionization (ESI)-MS, novel arsenic-containing long-chain fatty acids [21] and hydrocarbons [22] were identified in fish oil. Furthermore, the response factor of known concentration of arsenic (e.g.…”
Section: Speciation Of Asmentioning
confidence: 99%
“…[12,17,18] Recent findings of Meyer et al [19] have shown that AsHCs show different toxicity depending on the structure of the AsHC and can have similar cytotoxicity to inorganic arsenic (iAs). These new findings underline the relevance of accurately identifying AsLps but also the need to understand better how they are formed and which factors influence their formation.…”
Section: Introductionmentioning
confidence: 99%